IDENTIFIKASI SEBARAN INDIKASI AIR TANAH DANGKAL TERKONTAMINASI LINDI DENGAN MENGGUNAKAN METODE RESISTIVITAS DAN INDUCED POLARIZATION (IP) DI SEKITAR TPA SAMBUTAN KOTA SAMARINDA - Bamba, Ayub; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2019)
Sambutan of Samarinda City Landfill implements a sanitary landfill system in accordance with the applicable terms and conditions to minimize or eliminate environmental problems. This research was conducted around Sambutan of Samarinda which are in an area with coordinates 117 ° 06 '44.00 "BT, 00 ° 27' 36.00" LS - 117 ° 07 '11.00 "BT, 00 ° 27' 18.00" LS. In the five line was measured to obtain the values of apparent resistivity (ρa) and apparent chargeability (ma) each 3,250 data. These values are processed by the res2dinv program to obtain 2-D model. Furthermore, the modeling results are correlated to obtain 3-D models using Rockwork program. The results show that sanitary landfill waste treatment system does not have a negative impact on environment. The results of geoelectric modeling there is an indication of shallow groundwater which has the potential for leachate conta mination from lines 1 to 5 with a distribution of resistivity values 10.2 Ω.m to 81.6 Ω.m and distribution of chargeability values 6.32 msec to 10, 0 msec.